Controlled‐release oral melatonin supplementation for hypertension and nocturnal hypertension: A systematic review and meta‐analysis. Issue 5 (7th April 2022) - Lee, Eric Kam‐Pui; Poon, Paul; Yu, Chun‐Pong; Lee, Vivian Wing‐Yan; Chung, Vincent Chi‐Ho; Wong, Samuel Yeung‐Shan
Abstract: Oral melatonin is a potential alternative treatment for hypertension and nocturnal hypertension. However, high‐quality and relevant meta‐analyses are lacking. This meta‐analysis aimed to investigate whether oral melatonin supplementation reduces daytime/asleep blood pressure and cardiovascular risk, improves sleep quality, and is well‐tolerated compared with placebo. Relevant articles were searched in multiple databases, including MEDLINE, EMBASE, CINAHL Complete, and the Cochrane Library, from their inception to June 2021. The included studies were randomized controlled trials recruiting patients with hypertension, using oral melatonin as the sole intervention, and investigating its effect on blood pressure. The mean out‐of‐office (including 24‐h, daytime, and asleep) systolic and diastolic blood pressures, sleep quality, and side effects were compared between the melatonin and placebo arms using pairwise random‐effect meta‐analyses. A risk of bias assessment was performed using the Cochrane risk‐of‐bias tool. Four studies were included in the analysis and only one study was considered to have a low risk of bias. No study reported on cardiovascular risk or outcomes. Only controlled‐release melatonin (not an immediate‐release preparation) reduced asleep systolic blood pressure by 3.57 mm Hg (95% confidence interval: –7.88 to .73; I 2 = 0%). It also reduced asleep and awake diastolic blood pressure, but these differences were not statistically significant. Melatonin improves sleep efficacy and total sleep time and is safe and well‐tolerated. Due to the limited number of high‐quality trials, the quality of evidence was low to very low. Therefore, adequately powered randomized controlled trials on melatonin are warranted.